The Effect of Asthma Severity on Perinatal Outcomes: A Tertiary Hospital Experience - Tanacan, Atakan; Fadiloglu, Erdem; Celebioglu, Ebru Damadoglu; Orhan, Nazli; Unal, Canan; Celik, Tolga; Kalyoncu, Ali Fuat; Beksac, Mehmet Sinan (Zeitschrift für Geburtshilfe und Neonatologie, 2020)
Objective To evaluate the effect of asthma severity and disease exacerbation on pregnancy outcomes.Materials and Methods Pregnancies were classified into 3 groups as mild (n=195), moderate (n=63), and severe (n=26) according to preconceptional asthma severity. Demographic features, clinical characteristics, and perinatal outcomes were compared between the groups. Delivery characteristics and pregnancy outcomes were also compared between the pregnancies with or without asthma exacerbation (43 and 241 pregnancies, respectively).Results Worsening of symptoms during pregnancy was higher in moderate and severe asthma groups (p<0.001). Rates of spontaneous abortion, fetal structural anomaly, preterm delivery, preeclampsia, fetal growth restriction (FGR), oligohydramnios, gestational diabetes, and intrauterine fetal demise were higher in moderate and severe asthma groups (p-values were < 0.001, 0.01, 0.008, 0.02, 0.01, < 0.001, < 0.001, and 0.007, respectively). Admissions to neonatal intensive care units and neonatal complication rates were higher among moderate and severe asthma groups (p=0.035 and < 0.001). Spontaneous abortion, preterm delivery, preeclampsia, FGR, oligohydramnios, and neonatal complication rates were higher (p<0.001) in the group with exacerbated symptoms.Conclusion Moderate to severe asthma before pregnancy and the exacerbation of asthma symptoms during pregnancy may lead to increased rates of perinatal complications.
Keywords: antenatal care; high risk pregnancy; maternal risks; perinatal